2011
DOI: 10.1371/journal.pone.0028736
|View full text |Cite
|
Sign up to set email alerts
|

The Ratio 1660/1690 cm−1 Measured by Infrared Microspectroscopy Is Not Specific of Enzymatic Collagen Cross-Links in Bone Tissue

Abstract: In postmenopausal osteoporosis, an impairment in enzymatic cross-links (ECL) occurs, leading in part to a decline in bone biomechanical properties. Biochemical methods by high performance liquid chromatography (HPLC) are currently used to measure ECL. Another method has been proposed, by Fourier Transform InfraRed Imaging (FTIRI), to measure a mature PYD/immature DHLNL cross-links ratio, using the 1660/1690 cm−1 area ratio in the amide I band. However, in bone, the amide I band composition is complex (collagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 46 publications
2
69
0
Order By: Relevance
“…On the other hand, the maturity of the collagen matrix, determined as the 1660:1690 cm K1 ratio, was significantly reduced. Some controversies exist in the interpretation of this ratio as some groups reported that this ratio represent the trivalent over divalent cross-links ratio, but recently, an elegant study of Farlay and collaborators demonstrated that variation in this parameter could be more related to secondary structure of the collagen matrix after mineralization than a ratio of trivalent over divalent collagen cross-links (Farlay et al 2011). Nevertheless, it is an indicator of collagen maturity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the maturity of the collagen matrix, determined as the 1660:1690 cm K1 ratio, was significantly reduced. Some controversies exist in the interpretation of this ratio as some groups reported that this ratio represent the trivalent over divalent cross-links ratio, but recently, an elegant study of Farlay and collaborators demonstrated that variation in this parameter could be more related to secondary structure of the collagen matrix after mineralization than a ratio of trivalent over divalent collagen cross-links (Farlay et al 2011). Nevertheless, it is an indicator of collagen maturity.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluated IR spectral parameters were i) mineral-to-matrix ratio, which reflects the degree of mineralization of the bone matrix, calculated from the ratio of integrated areas of the phosphate y1, y3 band at 900-1200 cm K1 to the amide I band at 1585-1725 cm K1 ; ii) mineral maturity, which reflects the ratio of apatic vs nonapatic domains, calculated as the ratio of the relative intensity of sub-bands at 1020 and 1030 cm K1 of the phosphate band (Paschalis et al 1996); iii) carbonate-to-phosphate ratio was expressed by the ratio of integrated areas of the y2 CO 3 2K region (850-890 cm K1 ) to the y1, y3 phosphate band (900-1200 cm K1 ) (Boskey et al 2005); and iv) collagen maturity, determined as the relative ratio of sub-bands located at 1660 and 1690 cm K1 of the amide I peak. Although multiple theories about the significance of this ratio (pyridinium trivalent to dehydrodihydroxylysinonorleucine divalent collagen cross-links, modifications of secondary structure of collagen molecules) exist, this ratio indicates the maturity of the collagen of the bone matrix (Paschalis et al 2001, Farlay et al 2011.…”
Section: Fourier Transformed Infrared Spectroscopymentioning
confidence: 99%
“…12,13 Unsurprisingly, the interpretation of the 1660/1690 cm À 1 intensity ratio has been contentious, leading some to call it the matrix maturity ratio. 14 The ratio does depend on measurement conditions, especially if agents such as b-aminopropionitrile that perturb cross-linking are used. 15 Absolute measurements of Raman band intensities are difficult, especially in turbid media such as bone.…”
Section: Raman Intensitymentioning
confidence: 99%
“…Given the non-negligible interference of the non-collagenous molecules as well as the different extinction coefficients of water and collagen, there is a great uncertainty regarding the ratio measured. In addition, recent studies have correlated the 1660/1690 cm −1 ratio to mineral maturity and to the degree of mineralization rather than to the modification of the enzymatic cross-links [66]. Thus, such a measurement could reflect the change in the secondary structure of collagen related to the mineralization process as well as to the dehydration of the mineral phase.…”
Section: Band Analysis and Quantificationmentioning
confidence: 99%